Preliminary Phytochemical Studies Of Lantana Aculeata Roots - VINOTH KUMAR. K; DAWOOD SHARIEF. S; SUKUMAR. E (International Journal of Pharma and Bio Sciences, 2011)
Lantana aculeata, a sprawling weed belongs to the Verbenaceae family available in plenty in many parts of the Indian Subcontinent and is known for its variety of biological uses due to the presence of various phytoconstituents. The roots of the plant in general contain a plethora of active compounds with varied chemical structures. Mature roots extracts have been chosen for the present phytochemical investigation as no study on this part was reported so far.